Shared decision making in chronic kidney disease: a qualitative study of the impact of communication practices on treatment decisions for older patients - Maria R. Dahm; Suzanne Eggins Raine; Diana Slade; Laura J. Chien; Alice Kennard; Giles Walters; Tony Spinks; Girish Talaulikar (BMC Nephrology, 2023)
Abstract Background Effective interpersonal communication is critical for shared decision-making (SDM). Previous SDM communication training in nephrology has lacked context-specific evidence from ethnographic analysis of SDM interactions with older patients considering treatment options of end stage kidney disease (ESKD). This study explores communication strategies in SDM discussions in nephrology, specifically focusing on older patients considering dialysis as kidney replacement therapy (KRT). Methods We conducted a qualitative study analysing naturally-occurring audio-recorded clinical interactions (n = 12) between Australian kidney doctors, patients aged 60+, and carers. Linguistic ethnography and qualitative socially-oriented functional approaches were used for analysis. Results Two types of communication strategies emerged: (1) Managing and advancing treatment decisions: involving active checking of knowledge, clear explanations of options, and local issue resolution. (2) Pulling back: Deferring or delaying decisions through mixed messaging. Specifically for non-English speaking patients, pulling back was further characterised by communication challenges deferring decision-making including ineffective issue management, and reliance on family as interpreters. Age was not an explicit topic of discussion among participants when it came to making decisions about KRT but was highly relevant to treatment decision-making. Doctors appeared reluctant to broach non-dialysis conservative management, even when it appears clinically appropriate. Conservative care, an alternative to KRT suitable for older patients with co-morbidities, was only explicitly discussed when prompted by patients or carers. Conclusions The findings highlight the impact of different communication strategies on SDM discussions in nephrology. This study calls for linguistic-informed contextualised communication training and provides foundational evidence for nephrology-specific communication skills training in SDM for KRT among older patients. There is urgent need for doctors to become confident and competent in discussing non-dialysis conservative management. Further international research should explore naturally-occurring SDM interactions in nephrology with other vulnerable groups to enhance evidence and training integration.